2021
DOI: 10.1051/e3sconf/202127001040
|View full text |Cite
|
Sign up to set email alerts
|

Trends and conditions for the development of green energy in the Russian Federation

Abstract: The second decade of the twenty-first century was a turning point when the leaders of the largest and most developed countries began to talk about a gradual transition from traditional energy sources to renewable ones. This decision was made in connection with the growth of carbon dioxide emissions into the atmosphere, and, as a consequence, an increase in the temperature of the lower layers of the atmosphere due to the greenhouse effect. The purpose of the study is to identify effective practices and prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In addition, the attitude towards renewable energy sources (RES) and their development in the country are also interrelated: the result of a previous study showed that Russian residents do not consider green energy as promising that correlates with the pace of its development: traditional energy facilities prevail in Russia to a greater extent [5,[33][34][35]. Consequently, the attitude of society, in this case, may also be considered as one of the barriers to the development of renewable energy in Russia.…”
Section: Of 15mentioning
confidence: 99%
“…In addition, the attitude towards renewable energy sources (RES) and their development in the country are also interrelated: the result of a previous study showed that Russian residents do not consider green energy as promising that correlates with the pace of its development: traditional energy facilities prevail in Russia to a greater extent [5,[33][34][35]. Consequently, the attitude of society, in this case, may also be considered as one of the barriers to the development of renewable energy in Russia.…”
Section: Of 15mentioning
confidence: 99%